Prognostic factors and outcomes of infant acute lymphoblastic leukemia (ALL), hypodiploid ALL, and mixed-phenotype acute leukemia (MPAL) in Canada: a report from CYP-C. Issue 13 (10th November 2022) - Tibout, Pauline; Ledjiar, Omar; Athale, Uma; Rayar, Meera; Kulkarni, Ketan; Truong, Tony; Cellot, Sonia; Bittencourt, Henrique; Pelland-Marcotte, Marie-Claude; Tran, Thai Hoa
Abstract: The epidemiology of infant acute lymphoblastic leukemia (ALL), hypodiploid ALL, and mixed-phenotype acute leukemia (MPAL) in Canada is unknown. The main objective was to describe the prevalence, prognostic factors, and outcomes of three rare and high-risk ALL subtypes in Canada. This is a retrospective study using the Cancer in Young People-Canada (CYP-C) database. Event-free survival (EFS) and overall survival (OS) were described by the Kaplan–Meier method and compared using the log-rank test. Among 2626 children aged 0–14 years diagnosed with B-cell acute lymphoblastic leukemia (B-ALL) between 2001 and 2018, 227 (8.6%) patients were identified to be infant ALL ( n = 139), hypodiploid ALL ( n = 43), or MPAL ( n = 45). The 5-year EFS/OS was significantly worse in the infant ALL subgroup compared to that of hypodiploid ALL and MPAL. For the entire cohort, presenting White blood cells (WBCs) ≥50 × 10 9 /L was independently associated with worse EFS/OS.